MENAFSIR AYAT SABAR SEBAGAI BASIS TERAPI KESEHATAN MENTAL PASCA PANDEMI COVID-19 (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2023)
This article discusses the relation between the conception of patience and the issue of mental health in several verses of patience (QS. 2:45, QS. 2:153, and QS.:3) which are described in two treasures of interpretation: Tafsir At-Thabari and Tafsir Ar-Razi. The purpose of this research is to investigate the doctrine and teachings of patience as a knowledge base in supporting mental health theories spiritually, especially in the context of the Covid-19 pandemic. The method of investigation and discussion in research is more of a qualitative approach with the object of research being the Divine Word. A number of findings in this research review, among others: the unfolding of the doctrine and conception of patience holistically (exoteric and esoteric) as well as the foundation cum formulation of patient therapy in Islamic mental health discourses.